A Review of Efficacy and Safety of Checkpoint Inhibitor for the Treatment of Acute Myeloid Leukemia - Dan Liao; Mengyao Wang; Yi Liao; Jun Li; Ting Niu; Ting Niu (Frontiers in Pharmacology, 2019)
Immune checkpoint inhibitors (ICIs) as positive modulators of immune response have revolutionized the treatment of cancer and have achieved impressive efficacy in melanoma and numerous solid tumor malignancies. These agents are being investigated in acute myeloid leukemia (AML) to further enhance response rate as induction therapy and to improve relapse-free survival (RFS) post chemotherapy and bone marrow transplantation. PD-1 and CTLA-4 are the two most actively investigated checkpoint receptors, which play a role in different stages of anti-tumor immune response. This study reviews data from ongoing phase I, II clinical trials evaluating PD-1 and CTLA-4 inhibitors on AML patients and discusses especially efficacy and adverse events as well as prospects of these drugs in treating AML. Single anti-PD-1 monoclonal antibody infusion shows rather modest clinical efficacy. While combinations of PD-1 inhibitor with hypomethylating agents (HMAs) represent encouraging outcome for relapsed/refractory (R/R) AML patients as well as for elderly patients as first-line therapy option. Adding PD-1 inhibitor to traditional induction therapy regimen is also safe and feasible. CTLA-4 inhibitor ipilimumab exhibits specific potency in treating relapsed AML patients with extramedullary disease in later post-transplantation stage. In terms of side effects, irAEs found in these trials can mostly be appropriately managed with steroids but are occasionally fatal. More rationally designed combinational therapies are under investigation in ongoing clinical trials and will further advance our understanding of checkpoint inhibitors as well as lead us to the most appropriate application of these agents.